The preoperative hemoglobin, albumin, lymphocyte, and platelet score (HALP) as a prognostic indicator in patients with non-small cell lung cancer - Liu, Qiteng; Xie, Hailun; Cheng, Wenjuan; Liu, Tong; Liu, Chenan; Zhang, Heyang; Lin, Shiqi; Liu, Xiaoyue; Tian, Haiying; Li, Xiangrui; Zheng, Xin; Chen, Yue; et al. (Frontiers in Nutrition, 2024)
Background The Hemoglobin, Albumin, Lymphocyte, and Platelet score (HALP) is an inflammatory nutrition-related biomarker based on hemoglobin and albumin levels, as well as the lymphocyte and platelet load index, which has been reported to be associated with the prognosis of various types of tumors. This study aims to investigate the prognostic value of HALP in patients with non-small cell lung cancer (NSCLC). Methods A total of 2,428 patients with NSCLC were enrolled in the INSCOC study. Time-patient survival trends were validated using Kaplan–Meier curves and log-rank tests. The Restricted Cubic Spline function was used to analyze the relationship between the HALP index and overall survival (OS). The Cox regression model was used for univariate and multivariate analyses. Results The study included 2,053 patients with detailed biological information and follow-up data, consisting of 1,346 men (65.6%) and 707 women (34.4%). Within this cohort, 138 patients (6.7%) had stage I disease, 282 (13.7%) had stage II, 477 (23.2%) had stage III, and 1,156 (56.3%) had stage IV. A total of 536 patients (26.1%) underwent surgery, 1,494 (72.8%) received chemotherapy, and 271 (13.2%) received radiotherapy. The 1-, 2-, 3-, and 5-year survival rates for patients with NSCLC were 68.6, 48.6, 37.4, and 30.9%, respectively. The optimal cut-off for HALP was determined to be 29.71, with a sensitivity of 53.1% and specificity of 62.9%, leading to the categorization of patients into low (<29.71) (n = 963) and high (≥29.71) (n = 1,090) HALP groups. Patients with a high HALP demonstrated a significantly higher 5-year overall survival (OS) rate compared to those with a low HALP (38% vs. 23%, p < 0.001). Multivariable Cox proportional hazards regression analysis identified that low HALP was an independent risk factor for the survival of patients with non-small cell lung cancer. Conclusion The HALP index can be used as an independent prognostic factor for patients with NSCLC, offering clinicians a reference to identify high-risk patient with poor long-term prognoses and improve individualized treatment.